«Մանկութեան աւետարան»-ը` հայ միջնադարյան արգելված գրքերի ցանկերում - Մամյան, Մարի («Նաիրի» հրատ.)
Two contrasting approaches, negative and positive, emerged in the Middle Ages with regards to the Armenian “Gospel of the Infancy”. The negative perception of the apocryphon is attested, on the one hand, by Samuēl Anecʻi (1100/05-1185/90), according to whom, the Gospel was brought to Armenia by the Syrian heretics (Nestorians), and, on the other hand, by the fact that it was included on nearly all of the medieval lists of forbidden books. Moreover, the “Gospel of the Infancy” was not only among writings considered to be Nestorian, but also was an integral part of the prohibited books of unknown origin, such as the list of “secret” books copied by Mxitʻar Ayrivanecʻi (1230/35-1297/1300). Unlike the majority of banned books that disappeared over the centuries, however, the Gospel of the Infancy was not only able to escape destruction and survive, but also gained the love and sympathy of monks and common believers, reaching us through numerous Armenian manuscripts scattered all over the world. В армянском средневековье сформировались два противоположных, позитивный и негативный, подхода к “Евангелию детства”. Об отрицательном восприятии апокрифа можем судить с одной стороны по свидетельству Самуэла Анеци (1100/05-1185/90 гг.), согласно которому Евангелие было привезено в Армению сирийскими еретиками (несторианами), а с другой стороны, по тому факту, что апокриф был включен почти во все средневековые списки запрещенных книг. Речь идет не только о списках сочинений, считающихся несторианскими, но и о списках запрещенных книг, о происхождении которых нет прямых свидетельств, таких, например, как список “потаенных” книг, сохраненный Мхитаром Айриванци (1230/35-1297/1300 гг.). Однако, в отличие от большинства запрет-ных книг, исчезнувших в течение столетий, “Евангелие детства” не только сумело избежать забвения, но приобрело любовь и симпатию монахов и обычных верующих и дошло до нас в многочисленных армянских рукописях, разбросанных по всему миру.
Keywords: Բանասիրություն